The Effect of Zakat Fund Distribution and Economic Growth on Poverty in East Java Province - Erdhilla Pramesti; A'rasy Fahrullah (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
The goal of this study is to examine the relationship between zakat, economic growth, and poverty in East Java Province from 2003 to 2022, utilizing variables such as zakat money distribution, economic growth, and the number of poor people. The research approaches employed are the quantitative research approach and multiple regression analysis. Data on the distribution of zakat funds from financial statements published by BAZNAS East Java Province, economic growth percentage data from the Central Statistics Agency (BPS) website, and data on the number of poor people in East Java Province compiled from the Central Statistics Agency (BPS) website are the secondary data used. The study's findings revealed that the distribution of zakat monies influenced the direction of the negative coefficient on poverty. However, economic growth had no effect on poverty with a negative coefficient. The independent variable influences the dependent variable at the same time.